2019
DOI: 10.1186/s11671-019-2853-x
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Chitosan Nanobubbles for Ultrasound-Mediated Targeted Delivery of Doxorubicin

Abstract: Ultrasound-targeted delivery of nanobubbles (NBs) has become a promising strategy for noninvasive drug delivery. The biosafety and drug-transporting ability of NBs have been a research hotspot, especially regarding chitosan NBs due to their biocompatibility and high biosafety. Since the drug-carrying capacity of chitosan NBs and the performance of ultrasound-assisted drug delivery remain unclear, the aim of this study was to synthesize doxorubicin hydrochloride (DOX)-loaded biocompatible chitosan NBs and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Therefore, there is an urgent need to prepare nanoscale drug-loaded ultrasound contrast agents with high safety and definite efficacy. Ultrasonic response nanobubbles synthesized by chitosan, perfluorohexane and other natural materials in our previous research has been proved to have higher biosafety than other contrast agents in cell experiments (Meng et al, 2019;Zhou et al, 2019). They may have a broad prospect in clinical application.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, there is an urgent need to prepare nanoscale drug-loaded ultrasound contrast agents with high safety and definite efficacy. Ultrasonic response nanobubbles synthesized by chitosan, perfluorohexane and other natural materials in our previous research has been proved to have higher biosafety than other contrast agents in cell experiments (Meng et al, 2019;Zhou et al, 2019). They may have a broad prospect in clinical application.…”
Section: Introductionmentioning
confidence: 94%
“…An ultrasound-responsive chitosan DOX nanobubble system was synthesized to deliver DOX following ultrasound exposure. It was observed that almost twice the amount of DOX was released, compared to the nonultrasound-responsive system [ 204 ]. Ultrasound-responsive, polymeric nanobubbles were constructed to deliver both siRNA and PTX to treat hepatocellular carcinoma [ 205 ].…”
Section: Stimuli-responsive Polymeric Nanocarriers For Drug and Gmentioning
confidence: 99%
“…A study was conducted to synthesize DOX-loaded biocompatible chitosan NBs. Nanobubbles-mediated DOX uptake and apoptosis on Michigan cancer foundation-7 cells were measured with flow cytometry and the results showed it to have excellent drug loading capability and ultrasound enhancement [ 96 ]. A new ultrasound imaging contrast agent was introduced, where the NBs were conjugated to poly (lactic-co-glycolic acid) and carried DOX as a cancer drug.…”
Section: Medical Imagingmentioning
confidence: 99%